Screening of Thyroid Disorder among Pregnant Ladies in a Tertiary Hospital of Nepal - Shrestha, Biloni; Adhikari, P. (Nepal Medical College Journal, 2019)
Thyroid disorders (TD) are the second most common endocrine disorders seen in pregnancy. Many physiological changes in pregnancy lead to hypothyroidism in pregnancy. Hypothyroid in pregnancy is associated with many adverse maternal and fetal outcomes. Objective of this study was to find the prevalence of TD in pregnancy in Nepal Medical College Teaching Hospital (NMCTH), Antithyroid Peroxidase Antibody (TPO-Ab) positive cases with hypothyroidism and to evaluate maternal fetal outcome in hypothyroid pregnancies. This was a prospective hospital based observational study. The study was done in Department of Obstetrics and Gynecology, NMCTH from August 2018 to July 2019. Among 420 pregnant ladies 71.0% were euthyroid, 25.7% were hypothyroid (25.2%of subclinical and 0.5% overt), 3.3% were hyperthyroid (0.7% of overt) and 6.4% were TPO-Abpositive with hypothyroidism. Inspite of treatment, Gestational hypertention, Pre-eclampsea and LSCS is significantly high in hypothyroid pregnancy than euthyroid pregnancy. High prevalence of hypothyroidism in this study necessitates universal screening of TD at first trimester of pregnancy.